The well-being of Iranian adult citizens; is it related to mental health literacy? - Mahmoodi, Seyed Mohammad Hossein; Rasoulian, Maryam; Khodadoust, Elaheh; Jabari, Zahra; Emami, Sahar; Ahmadzad-Asl, Masoud (Frontiers in Psychiatry, 2023)
Background Subjective well-being (SWB) is a fundamental concept in the definition of mental health and is a significant health indicator for individuals and societies. Mental health literacy (MHL) is a modifiable variable with known effects on mental health, but its relationship with SWB is not recognized. In this study, the SWB is measured, and its relationship to MHL is investigated. Methods In this cross-sectional study conducted in Iran in 2019, 1,682 individuals participated using a convenient sampling method. Participants with a basic ability to use internet were included. A simple online form was used to collect data. SWB and MHL were measured with three questionnaires: WHO-5 Well-Being Index, Mental Health Literacy Scale, and Mental Health Positive Knowledge. Results Most of the participants were young (mean age 25.99, SD 9.14), female (71.9%), and had a university degree (78.5%). The mean SWB was 50.19 out of 100 (SD 20.92). More than half of the participants (50.4%) were screen-positive for clinical depression regarding their low well-being. Significant but very small correlations were detected between SWB and both MHL measures. Conclusion The well-being of half of the educated Iranian citizens who participated in this study was poor and lower than previous measurements. No strong correlation is detected between SWB and MHL measures in this study. This suggests that people’s well-being cannot be improved by merely implementing mental health educational programs.